The Implementation of the Res Judicata Pro Veritate Habetur Principle to the Investigation of Money Laundering - Irpan Suriadiata (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to determine the position of court rulings on predicate crimes under the principle of Res Judicata Pro Veritate Habetur in money laundering cases, along with the legal rationale utilized by judges in adjudicating TPPU cases involving predicate crimes as specified in Article 127 paragraph (1) of the Narcotics Law. This study utilizes a normative-empirical approach through a case study method. This research is supported by the review of case files, the observation of trial proceedings, and the analysis of literature from various criminal law sources and relevant statutes and regulations. The utilized data analysis method is judicial-normative. The findings of this study reveal a violation of the principle of Res Judicata Pro Veritate Habetur in the evaluation of money laundering offenses, as demonstrated by the Mataram District Court Decision No. 516/Pid.Sus/2022/PN.Mtr, alongside the NTB High Court Decision No. 23/PID.Sus. 2023/PT.MTR, and the MARI Decision No. 4075 K/PID.Sus/2023, which neglected to account for the legally binding narcotics criminal ruling that serves as the predicate crime for the money laundering allegation. Both panels of judges committed errors in their legal reasoning by inadequately and incompletely assessing the predicate crime of narcotics offenses under Article 127, paragraph 1 of the Narcotics Law, concerning the evidence of 0.17 grams in relation to the sentencing and confiscation of the defendant's assets.